Strategi Branding Cameo Project dalam Meningkatkan Minat Masyarakat terhadap Layanan Streaming Vision Plus - Kurniawan, Zefanya Elizabeth; Kristiyani, Dian Novita (Peneliti.net, 2025)
Cameo Project is a production house owned by MNC Media that produces movies and television series aired on Vision Plus streaming service. In its implementation facing obstacles as a streaming service that has not been widely recognized, marketing activities are carried out based on four types of branding strategies. The strategies carried out aim to introduce to increase the number of subscribers. This research method uses a qualitative method with a phenomenon approach. Data collection uses interview, observation, and documentation techniques. The results showed that the branding strategy was carried out with a product line strategy through the expansion of Television Channel, Vision Sports, Vision Series, and K-Drama products. Brand extension strategy by adding live streaming shows of futsal, volleyball, basketball, and badminton to the Vision Sport category. Multi brand strategy through the addition of Vision+ TV which can be accessed through television. Co-branding strategy by collaborating with local and international brands to offer special packages. All these activities have had a positive impact on the increase in subscriber numbers but Vision Plus is not yet a favourite choice that is in the top position with other competitors.